Functional Diversity of Cytomegalovirus–Specific T Cells Is Maintained in Older People and Significantly Associated With Protein Specificity and Response Size. (11th August 2016) - Bajwa, Martha; Vita, Serena; Vescovini, Rosanna; Larsen, Martin; Sansoni, Paolo; Terrazzini, Nadia; Caserta, Stefano; Thomas, David; Davies, Kevin A.; Smith, Helen; Kern, Florian
Abstract: Background. Parallel upregulation of several T-cell effector functions (ie, polyfunctionality) is believed to be critical for the protection against viruses but thought to decrease in large T-cell expansions, in particular at older ages. The factors determining T-cell polyfunctionality are incompletely understood. Here we revisit the question of cytomegalovirus (CMV)–specific T-cell polyfunctionality, including a wide range of T-cell target proteins, response sizes, and participant ages. Methods. Polychromatic flow cytometry was used to analyze the functional diversity (ie, CD107, CD154, interleukin 2, tumor necrosis factor, and interferon γ expression) of CD4 + and CD8 + T-cell responses to 19 CMV proteins in a large group of young and older United Kingdom participants. A group of oldest old people (age >85 years) was included to explore these parameters in exceptional survivors. Polyfunctionality was assessed for each protein-specific response subset, by subset and in aggregate, across all proteins by using the novel polyfunctionality index. Results. Polyfunctionality was not reduced in healthy older people as compared to young people. However, it was significantly related to target protein specificity. For each protein, it increased with response size. In the oldest old group, overall T-cell polyfunctionality was significantly lower. Discussion. Our results give a new perspective on T-cell polyfunctionality and raise the question of whether maintaining polyfunctionality of CMV-specific T cells at older ages is necessarily beneficial.